2022
DOI: 10.3389/fmicb.2022.1024001
|View full text |Cite
|
Sign up to set email alerts
|

Apple Endophytic fungi and their antagonism against apple scab disease

Abstract: Endophytic fungi are microorganisms with the ability to colonize plants for the entire or at least a significant part of their life cycle asymptomatically, establishing a plant-fungus association. They play an important role in balancing ecosystems, as well as benefiting host through increasing plant growth, and protecting the host plants from abiotic and biotic stresses using various strategies. In the present study, endophytic fungi were isolated from wild and endemic apple cultivars, followed by characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 63 publications
(71 reference statements)
0
5
0
Order By: Relevance
“…Thus, we hypothesized that unlike endophytic fungi, endophytic bacteria are not actively involved in the resistance of sweetpotato to the scab pathogen. Ebrahimi et al [25] also reported similar results, whereby the endophytic fungi isolated from healthy apple fruits and apple tree leaves and branches had strong antifungal properties and could produce media-permeable metabolites, volatile organic compounds (VOCs), chitinases, and cellulases and promote phosphate solubilization as growth-promoting effects.…”
Section: Discussionmentioning
confidence: 77%
“…Thus, we hypothesized that unlike endophytic fungi, endophytic bacteria are not actively involved in the resistance of sweetpotato to the scab pathogen. Ebrahimi et al [25] also reported similar results, whereby the endophytic fungi isolated from healthy apple fruits and apple tree leaves and branches had strong antifungal properties and could produce media-permeable metabolites, volatile organic compounds (VOCs), chitinases, and cellulases and promote phosphate solubilization as growth-promoting effects.…”
Section: Discussionmentioning
confidence: 77%
“…Namely, the antifungal compound, berkedrimane B,(55) produced by T. minioluteus was found to be 28 times higher in black apples on average compared to on standard cultivation media. Pinselin and moniliphenone, biosynthetic precursors to the antifungal compound, chloromonilicin,(37) by M. fructigena were also [15][16][17][18][19][20][21][22][23][24][25] times more abundant in black apples. Whilst the Monilinia-derived chloromonilicin and chloromonilinic acid A were not detected in the OSMAC study as per the LCMS analysis conducted in the positive ionization mode, the compounds were identified in 9 and 20 of the black apple extracts, respectively.…”
Section: Relative Abundances Of Fungal Secondary Metabolites Indicate...mentioning
confidence: 99%
“…(6) Some of these fungi can inhibit the apple scab disease fungus Venturia inequalis . (15) However, these endophytic fungi do not produce a soft apple rot. Other species associated to rot of pomaceous fruits have included Talaromyces minioluteus and T. rugulosus (16) in addition to Trichothecium roseum (pink rot of apples).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the rot on the surface of apples, other species of filamentous fungi can cause dry rot diseases in apples (at the core) including Fusarium, Alternaria, and Trichoderma species ( 6 ). Some of these fungi can inhibit the apple scab disease fungus Venturia inequalis ( 15 ). However, these endophytic fungi do not produce a soft apple rot.…”
Section: Introductionmentioning
confidence: 99%